The Problems of Law and Ethics in the Periodicals of Northern Lithuania - Gaučaitė, Modesta (Žurnalistikos tyrimai, 2017)
This bachelor thesis focuses on the problems of law and ethics in the periodicals of Northern Lithuania. Ten newspapers from seven regions of Northern Lithuania were analyzed, looking for possible violations of The Lithuanian Ethical code of journalists and publishers and The Lithuanian Republic law of public information. Newspapers from the regions of Akmenė, Biržai, Joniškis, Mažeikiai, Pakruojis, Pasvalys and Šiauliai were analyzed. Apart from the research that was contucted, the thesis present the self-regulation and law system of Lithuanian media. In the first part of the thesis there are presentations of Lithuanian committee of journalists ethics as well as the Lithuanian Ethical code of journalists and publishers. In the same chapter information about The Law of public information, Inspector of journalists ethics and Committee of Lithuanian radio and television is given. Using iliustrations and information from Lithuanian and foreign authors an insight into Lithuanian media system is given. The second part of the bachelor thesis is the research and analysis of the ten newspapers. All of the newspapers that were analyzed are only published in the particular regions. There are not published nationally. 1456 of published newspapers issues were analyzed. In all these newspapers 127 publications with possible violations of The Ethical code of journalists and publishers and 25 publications with possible violations of The law of public infomation were found. The possible violations that were found most often were: advertisment published as impartial information, identities that could not be public were revealed, information about family conflicts were published, disturbing pictures were published. Newspaper that had the most possible violations was Akmenės “Vienybė”. It had 35 publications with possible violations. 20 of those 35 publications were advertisment related. Other newspapers had somewhat between 6 and 20 publications with possible violations. The conclusion that was made says that it is nessessary to talk about the fact that journalists in Lithuania are not required to have university or college degree. They lack professionalism and excellence. That is one of the reasons for all the violations of law and ethics in the media.
Keywords: ...